2005
DOI: 10.1016/j.febslet.2005.06.090
|View full text |Cite
|
Sign up to set email alerts
|

GABA, progesterone and zona pellucida activation of PLA2 and regulation by MEK‐ERK1/2 during acrosomal exocytosis in guinea pig spermatozoa

Abstract: We investigated whether GABA activates phospholipase A 2 (PLA 2 ) during acrosomal exocytosis, and if the MEK-ERK1/2 pathway modulates PLA 2 activation initiated by GABA, progesterone or zona pellucida (ZP). In guinea pig spermatozoa prelabelled with [14 C]arachidonic acid or [ 14 C]choline chloride, GABA stimulated a decrease in phosphatidylcholine (PC), and release of arachidonic acid and lysoPC, during exocytosis. These lipid changes are indicative of PLA 2 activation and appear essential for exocytosis sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
1
20
0
1
Order By: Relevance
“…The above results led us to hypothesize that AKAP4 can play a role in regulating spermatozoa cAMP/PKA and the PKC/ERK1/2 pathways, both known to regulate sperm biology324252627282930373839. We therefore examined the effect of cAMP upon PMA-stimulated ERK1/2 activity in the presence or absence of proAKAP4 in HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…The above results led us to hypothesize that AKAP4 can play a role in regulating spermatozoa cAMP/PKA and the PKC/ERK1/2 pathways, both known to regulate sperm biology324252627282930373839. We therefore examined the effect of cAMP upon PMA-stimulated ERK1/2 activity in the presence or absence of proAKAP4 in HEK293T cells.…”
Section: Resultsmentioning
confidence: 99%
“…At the very least, P enhances hamster sperm hyperactivation through both Ca 2+ signals and protein phosphorylations [5, 6, 8, 9, 12, 16, 30]. Moreover, it has been suggested that GABA induces the AR and capacitation in human, ram, rat, guinea pig and bull spermatozoa [19, 21, 23, 33,34,35,36]. Although in these species it is suggested that the effects of GABA on the AR and capacitation are the same as those of P, the regulatory mechanisms vary.…”
Section: Discussionmentioning
confidence: 99%
“…In human spermatozoa, it has been suggested that both the GABA A and GABA B receptors block stimulation of the AR by follicular fluid [34]. In guinea pig spermatozoa, GABA regulates the AR through activation of phospholipase A 2 , protein kinase C and the mitogen-activated protein kinase cascade [35]. Therefore, it is not possible to propose a universal GABA signal pathway regulating sperm function.…”
Section: Discussionmentioning
confidence: 99%
“…All guinea pigs were housed and then euthanized. The spermatozoa from guinea pig vas deferens and cauda epididymis were washed for 18 min at 600 3 g through a Percoll gradient (85%-55%-35%) and were adjusted to 2-3 3 10 7 cells/ml (unless indicated otherwise), resuspended in complete or Cl À -deficient MCM, and incubated at 38.58C for 6 h [29,34]. Sperm capacitation was evaluated by the induction of rapid synchronization of the AR following the addition of 2 mM Ca 2þ and progesterone or ZP [29,35].…”
Section: Evaluation Of Sperm Capacitationmentioning
confidence: 99%